2022
DOI: 10.3389/fnagi.2022.992873
|View full text |Cite
|
Sign up to set email alerts
|

A novel dual-task paradigm with story recall shows significant differences in the gait kinematics in older adults with cognitive impairment: A cross-sectional study

Abstract: ObjectiveCognitive and motor dysfunctions in older people become more evident while dual-tasking. Several dual-task paradigms have been used to identify older individuals at the risk of developing Alzheimer’s disease and dementia. This study evaluated gait kinematic parameters for dual-task (DT) conditions in older adults with mild cognitive impairment (MCI), subjective cognitive decline (SCD), and normal cognition (NC).MethodThis is a cross-sectional, clinical-based study carried out at the Zhongshan Rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Presently, some methods are available for detecting neurodegenerative diseases. Using data collected from question assessments [13], blood biomarkers [14], eye-tracking parameters [15], kinematic gait parameters [16], electroencephalograms (EEG) [17], and other tests, conclusions are drawn regarding the presence or high risk of developing PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, some methods are available for detecting neurodegenerative diseases. Using data collected from question assessments [13], blood biomarkers [14], eye-tracking parameters [15], kinematic gait parameters [16], electroencephalograms (EEG) [17], and other tests, conclusions are drawn regarding the presence or high risk of developing PD.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, five different frequency bands are investigated in EEG signals depending on their application. These bands are delta (0-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12)(13), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Their findings revealed that a classifier based on dual-task gait features could detect older adults who scored low on the Mini-Mental State Examination (MMSE) test [ 20 ]. In addition, Ali et al [ 21 ] used the Vicon Nexus 2.8 motion capture system to obtain kinematic gait parameters such as velocity, peak knee extension angle, and dual-task cost for participants. Their study showed that the kinematic gait parameters of the dual-task peak knee extension angle for story recall gait could effectively differentiate the MCI group from the healthy control (HC) group.…”
Section: Introductionmentioning
confidence: 99%